Pulmonary hypertension detection by computed tomography pulmonary transit time in heart failure with reduced ejection fraction. (6th December 2019) - Colin, Geoffrey C; Pouleur, Anne-Catherine; Gerber, Bernhard L; Poncelet, Pierre-Antoine; de Meester, Christophe; D'Hondt, Anne-Marie; Vlassenbroek, Alain; Houard, Laura; Gevenois, Pierre-Alain; Ghaye, Benoit
Abstract: Aims: To evaluate the relationships between pulmonary transit time (PTT), cardiac function, and pulmonary haemodynamics in patients with heart failure with reduced ejection fraction (HFrEF) and to explore how PTT performs in detecting pulmonary hypertension (PH). Methods and results: In this prospective study, 57 patients with advanced HFrEF [49 men, 51 years ± 8, mean left ventricular (LV) ejection fraction 26% ± 8] underwent echocardiography, right heart catheterization, and cardiac computed tomography (CT). PTT was measured as the time interval between peaks of attenuation in right ventricle (RV) and LV and was compared between patients with or without PH and 15 controls. PTT was significantly longer in HFrEF patients with PH (21 s) than in those without PH (11 s) and controls (8 s) ( P < 0.001) but not between patients without PH and controls ( P = 0.109). PTT was positively correlated with pulmonary artery wedge pressure (PAWP) ( r = 0.74), mean pulmonary artery pressure ( r = 0.68), N-terminal pro-B-type natriuretic peptide ( r = 0.60), mitral ( r = 0.54), and tricuspid ( r = 0.37) regurgitation grades, as well as with LV, RV, and left atrial volumes ( r from 0.39 to 0.64) ( P < 0.01). PTT was negatively correlated with cardiac index ( r = −0.63) as well as with LV ( r = −0.66) and RV ( r = −0.74) ejection fractions. PAWP, cardiac index, mitral regurgitation grade, and RV end-diastolic volume were all independent predictors of PTT. PTT value ≥14 s best-detected PH with 91% sensitivity and 88% specificity (area under the receiver operating characteristic curve: 0.95). Conclusion: In patients with HFrEF, PTT correlates with cardiac function and pulmonary haemodynamics, is determined by four independent parameters, and performs well in detecting PH.